2008
DOI: 10.1139/f08-164
|View full text |Cite
|
Sign up to set email alerts
|

Continental-scale variation in otolith geochemistry of juvenile American shad (Alosa sapidissima)

Abstract: Abstract:We assembled a comprehensive atlas of geochemical signatures in juvenile American shad (Alosa sapidissima) to discriminate natal river origins on a large spatial scale and at a high spatial resolution. Otoliths and (or) water samples were collected from 20 major spawning rivers from Florida to Quebec and were analyzed for elemental (Mg:Ca, Mn:Ca, Sr:Ca, and Ba:Ca) and isotope ( 87 Sr: 86 Sr and d 18 O) ratios. We examined correlations between water chemistry and otolith composition for five rivers whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 46 publications
3
47
2
1
Order By: Relevance
“…Significant correlations between water and otolith signatures for these three naturally occurring chemical markers are consistent with results of prior studies (Patterson et al, 1993;Wells et al, 2003;Walther and Thorrold, 2008). Observed differences in water and otolith  18 O between the Illinois River and its floodplain lakes are likely due primarily to the greater opportunity for evaporative fractionation (Hoefs, 2004) to be expressed in floodplain lakes as a result of their longer water residence times relative to the Illinois River.…”
Section: Methodssupporting
confidence: 84%
“…Significant correlations between water and otolith signatures for these three naturally occurring chemical markers are consistent with results of prior studies (Patterson et al, 1993;Wells et al, 2003;Walther and Thorrold, 2008). Observed differences in water and otolith  18 O between the Illinois River and its floodplain lakes are likely due primarily to the greater opportunity for evaporative fractionation (Hoefs, 2004) to be expressed in floodplain lakes as a result of their longer water residence times relative to the Illinois River.…”
Section: Methodssupporting
confidence: 84%
“…The stressful periodic hypoxia decreased otolith Mg:Ca as would be expected if Mg is under endogenous control, but otolith Ba:Ca also decreased. In many euryhaline species, otolith Ba:Ca typically displays positive relationships with ambient dissolved Ba, as observed in both controlled lab experiments (Bath et al 2000, Elsdon & Gillanders 2002, 2003, 2004, 2005, Bath Martin & Thorrold 2005, Walther & Thorrold 2006, Miller 2009, and field studies (Dorval et al 2007, Walther & Thorrold 2008, Mohan et al 2012). Some studies have found an effect of somatic/otolith growth on otolith Ba:Ca (Walther et al 2010, Miller 2011 Interestingly, the periodic hypoxia treatment did result in significant Sex × Treatment interactions for otolith Sr:Ca and Na:Ca ratios and also decreased both otolith Ba:Ca and Mg:Ca ratios, perhaps because alternating between hypoxic and normoxic conditions is more physiologically stressful than remaining in constant hypoxic conditions.…”
Section: Effects Of Sex and Stress On Otolith Chemistrymentioning
confidence: 72%
“…Walther and coworkers initially identified unique geochemical signatures in otoliths of young-of-the-year American shad (Alosa sapidissima) from a total of 20 rivers along the east coast of the United States (Walther and Thorrold 2008). They then used river-specific values in d 18 O, 87 Sr : 86 Sr, Sr : Ca, and Ba : Ca in the core region of adult otoliths to determine natal origins of ocean-phase subadults collected in the Gulf of Maine (Walther and Thorrold 2010).…”
Section: Applicationsmentioning
confidence: 99%